PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 25 PADANG - Putri, Windi Pratama; Jamaan, Elita Zusti (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students must prioritise learning results. Eighth grade students of SMPN 25 Padang had low mathematics learning outcomes. PBL was used to address this problem. This study examines how Problem-Based Learning (PBL) affects students' mathematics learning outcomes and compares it with direct teaching. Descriptive research and pseudo-research using Non-Equivalent Posttest-Only Control Group Design were used. The samples of this study were students of class VIII.4 and VIII.6 SMP Negeri 25 Padang. This study found that students who participated in PBL had better scores in mathematics compared to students who participated in direct learning.Keywords– Learning Outcomes, Problem Based Learning, Direct Learning